RECREATING A SOCIETY’S MATERIAL CULTURE: TEXTILES IN THE TRIKKE CODEX EBE 1471 - Vryzidis, Nikolaos (Analecta Stagorum et Meteororum, 2022)
The Trikke codex EBE 1471 preserves a variety of documents, many of which are of interest to historians of material culture. In particular, church inventories, wills, and dowries are especially rich in mentions of different textiles: from the most luxurious cloths of gold to the more modest block-printed cottons. By drawing upon this valuable source, I will offer an as representative as possible compendium of the textiles consumed in the wider Trikke region from the late seventeenth century and on. The great variety of weavings and provenances mentioned in the codex certainly provides ample ground for an analysis of the textile trends prevailing in West Thessaly. Finally, by pairing the textual information with actual remnants this study aims at visualizing the specific period’s eclectic aesthetic and cultural interconnectedness, thereby illuminating its place in the early modern “geography of cloth”, and the dynamics woven within it.